The combined effects of alcohol and tobacco use during pregnancy on birth outcomes - Jadwiga Hamułka; Monika A. Zielińska; Katarzyna Chądzyńska (National Institute of Public Health - National Institute of Hygiene, 2018)
Background: Exposure to alcohol and tobacco during pregnancy may lead to developmental disorders in the foetus and can also adversely impact pregnancy outcomes and the newborn's health status. Objective: Assessment of alcohol consumption and tobacco use during pregnancy as well as their impact on pregnancy outcomes and birth parameters of the newborn in a selected group of mothers with children aged ≤ 2 years. Material and methods: The study was conducted in 104 mothers with children aged ≤ 2 years living in the Mazowiecki Voivodeship. A questionnaire was used for assessing selected lifestyle parameters tobacco and alcohol use, dietary supplements use, physical activity during pregnancy, socio-demographic characteristics as well as children's birth parameters (birth weight, length, head circumference, chest circumference). Data were analyzed statistically using logistic regression analysis, Spearman's rang correlation, the Mann-Whitney U, Kruskal-Wallis, Student-t, Tukey and Chi2 tests (p≤0.05; STATISTICA 13.1 PL). Results: 22% of the participants solely smoked cigarettes, 13% solely drank alcohol while 7% smoked cigarettes and drank alcohol. Both cigarette smoking and alcohol use increased the risk of preterm birth (OR 9.6, 95% CI 2.9 - 31.4, p=0.00015; OR 5.3 95% CI 1.3 - 22.3, p=0.0199, respectively) as along with a low birth weight (OR 6.9, 95% CI 1.9 - 25.2, p=0.0028; OR 7.6, 95% CI 1.7 - 34.3, p=0.007). Cigarette smoking and alcohol use by the pregnant women also adversely impacted on children's health status (8.7 ± 1.4 vs. 9.7 ± 0.8, p=0.001 and 8.5 ± 1.9 vs. 9.6 ± 0.8, p=0.027, respectively). Simultaneous use of alcohol and cigarettes exacerbated the adverse impact of such substances on birth parameters and health status (birth weight, body length, Apgar score) as well as on pregnancy duration. Conclusions: The introduction of educational programs for high risk groups as well as prenatal obligatory consultations for mothers about the negative effects of substance use on fetus and the development of the child are warranted. Conclusions: Introducing educational programs are thus warranted for high risk groups as well as prenatal obligatory consultations for mothers about the adverse effects of such substance use on foetal and child development.